THE INFLUENCE OF LEARNING FACILITIES AND IMPLEMENTATION OF E-LEARNING ON INTEREST IN LEARNING HISTORY IN THE COVID-19 PANDEMI TIME FOR STUDENTS IN CLASS XI IPS SMA PANGUDI LUHUR ST. LOUIS IX SEDAYU ACADEMIC YEAR 2021/2022 - Risdiyanto, Riko; Fahruddin (Satmata: Journal of Historical Education Studies, 2023)
This study aims to determine: (1) How good the learning facilities at home are to the interest in learning history of students in class XI Social Sciences at SMA Pangudi Luhur St. Louis IX Sedayu in the subject of history for the academic year 2021/2022; (2) How well is the application of e-learning to the interest in learning history of students in class XI IPS SMA Pangudi Luhur St. Louis IX Sedayu for the academic year 2021/2022; (3) How high is the interest in learning history of students in class XI IPS SMA Pangudi Luhur St. Louis IX Sedayu for the academic year 2021/2022; (4) The large influence of learning facilities at home on the interest in learning history of students in class XI IPS SMA Pangudi Luhur St. Louis IX Sedayu for the academic year 2021/2022; (5) The influence of the application of e-learning on the interest in learning history of students in class XI IPS SMA Pangudi Luhur St. Louis IX Sedayu for the academic year 2021/2022; (6) The influence of learning facilities at home and the application of e-learning on the interest in learning history of students in class XI IPS SMA Pangudi Luhur St. Louis IX Sedayu for the academic year 2021/2022. This study uses a survey method, with a quantitative approach. The population in this study was taken from 20% of the total population, as many as 12 students of class XI IPS SMA Pangudi Luhur St. Louis IX Sedayu for the academic year 2021/2022, with an error rate of 5%, and has been tested for validity and reliability. The analysis prerequisite tests in this study were the normality test, linearity test, multicollinearity test, and heteroscedasticity test. The analysis technique used is Product Moment Correlation analysis technique, multiple linear analysis, t test and f test. The results showed that: (1) The level of learning facilities at home was 85% included in the very good category; (2) The level of application of e-learning is 79% which is included in the good category; (3) The level of interest in learning history is 89% included in the very good category; (4) There is a positive, very strong and significant effect on the 5% error level between home learning facilities on interest in learning history of 0.986; (5) There is a positive, very strong and significant effect on the 5% error level between the application of e-learning to interest in learning history of 0.928; (6) There is a positive, very strong and significant effect at the 5% error level between home learning facilities and the application of e-learning with an interest in learning history of 0.987.